Teaching your baby to sign - Heller, Lora. (New York : Sterling Pub. Co., 2004)
Color photos illustrate 22 signs.
Cover title.
On board pages.
Keywords: Nonverbal communication in infants; Interpersonal communication in infants; Child rearing; Sign language; American Sign Language; Sign language